2010
DOI: 10.3897/compcytogen.v4i2.36
|View full text |Cite
|
Sign up to set email alerts
|

Bed bug cytogenetics: karyotype, sex chromosome system, FISH mapping of 18S rDNA, and male meiosis in Cimex lectularius Linnaeus, 1758 (Heteroptera: Cimicidae)

Abstract: Abstract. Bugs (Insecta: Heteroptera) are frequently used as examples of unusual cytogenetic characters, and the family Cimicidae is one of most interest in this respect. We have performed a cytogenetic study of the common bed bug Cimex lectularius Linnaeus, 1758 using both classical (Schiff-Giemsa and AgNO 3 -staining) and molecular cytogenetic techniques (base-specifi c DAPI/CMA 3 fl uorochromes and FISH with an 18S rDNA probe). Males originated from a wild population of C. lectularius were found to have 2n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 33 publications
6
60
1
Order By: Relevance
“…Oncopeltus femoralis showed an 18S rDNA interstitial site in an autosomal bivalent; Ochrimnus sagax showed this sequence in the largest autosomal bivalent in the interstitial terminal region, whereas, in Lygaeus peruvianus, the rDNA cistrons were found in the interstitial region of an autosomal pair. In Heteroptera, studies focusing on the identification and localization of 18S rDNA on chromosomes are restricted to a few species of some families and the results have shown that the 18S rRNA gene might be located in both the autosomes and the sex chromosomes (Papeschi et al, 2003;Bardella et al, 2010;Grozeva et al, 2010;Poggio et al, 2011;Panzera et al, 2012). However, most of the studies revealed that these cistrons at terminal position of the chromosomes were different from those found in the species analyzed in this study.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Oncopeltus femoralis showed an 18S rDNA interstitial site in an autosomal bivalent; Ochrimnus sagax showed this sequence in the largest autosomal bivalent in the interstitial terminal region, whereas, in Lygaeus peruvianus, the rDNA cistrons were found in the interstitial region of an autosomal pair. In Heteroptera, studies focusing on the identification and localization of 18S rDNA on chromosomes are restricted to a few species of some families and the results have shown that the 18S rRNA gene might be located in both the autosomes and the sex chromosomes (Papeschi et al, 2003;Bardella et al, 2010;Grozeva et al, 2010;Poggio et al, 2011;Panzera et al, 2012). However, most of the studies revealed that these cistrons at terminal position of the chromosomes were different from those found in the species analyzed in this study.…”
Section: Discussioncontrasting
confidence: 46%
“…In Hemiptera, these studies have revealed important findings compared to those obtained in other groups of insects (Caterino et al, 2000). Besides 18S rDNA, other classes of repetitive DNA with heterochromatic sequences have also been widely used as cytogenetic markers for comparisons across different groups of insects such as in Orthoptera (Cabral-de-Mello et al, 2011), Coleoptera (Almeida et al, 2010), Diptera (Rafael et al, 2006), and Heteroptera Bardella et al, 2010;Grozeva et al, 2010;Panzera et al, 2012). Some types of repetitive DNA can be chromosomespecific, such as those mostly found in Drosophila melanogaster (Bonaccorsi and Lohe, 1991) and those found on the sex chromosomes in species such as Megoura (Bizzaro et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most probably the observed differences reflect variation in the copy number of rRNA genes either between different chromosome pairs or between two homologous chromosomes. This can be attributed to various mechanisms, including unequal crossing over, transposition, tandem amplification and other rearrangements involving homologous segments, yielding structural modification of NORs (Castro et al, 2001) The heteromorphism in size and intensity of NORs has been frequently reported in aphids (Monti et al, 2011 and reference therein), heteropterans (Grozeva et al, 2010), orthopterans (Warchałowska-Śliwa et al, 2009), as well as certain other insect orders.…”
Section: Discussionmentioning
confidence: 99%
“…Leston 1957, Piza 1957, Warren et al 1960, Ueshima 1963 and it is still considered as a classical method by the majority of insect cytogeneticists including heteropterologists (e.g. Bressa et al 2002a, Poggio et al 2006, Grozeva et al 2010, Yang et al 2012.…”
Section: Introductionmentioning
confidence: 99%